High quality micromachined inductors for integrated communication systems - Carazzetti, Patrick (My University, 2006)
High-performance RF inductors have been fabricated with innovative and low-thermal budget micromachining processes. The proposed inductors have been implemented as single-level planar spirals so as to simplify their fabrication. Skin and proximity effects in the metal tracks have been addressed by providing thick layers of Al or Ag and by designing circular and hollow spirals. Energy dissipation in the substrate has been mitigated by using high-resistivity Si (HRS) or Pyrex. Al films ranging from 3 up to 8 µm have been sputter deposited and patterned into spirals with an anisotropic ICP dry-etching process. Vertical patterns with aspect ratio of 1.33 have been demonstrated on 8 µm-thick films. Such characteristic allows for a tight magnetic coupling between adjacent tracks and for the consequent maximization of the inductance per unit area. On the other hand, Ag electroplating into polymer molds has made possible the fabrication of spirals up to 12 µm-thick. Both Al and Ag films have shown excellent values of conductivity. An empirical study of inductor performances has been carried out in order to provide a physical insight on the role played by the type of substrate, spiral conductivity and layout parameters. Inductors fabricated on Pyrex achieve better performances in terms of Q-factor and self-resonance than their counterparts implemented on HRS. Particularly, peak values of Q-factor exhibit an improvement of 30-40%, while fSR raises by about 1-2 GHz. Q-factor up to 50 at 4.5 GHz and self-resonance above 10 GHz have been exhibited by a 5 nH Ag inductor on Pyrex. In comparison, a peak-Q of 38 has been obtained from an inductor with identical layout fabricated with an 8 µm-thick Al spiral. Measured data of inductors have been accurately matched with an equivalent compact model based on frequency-independent elements. Such a model enables the extraction of the relevant parameters describing the inductor behavior as a function of frequency. Accurate matching of the measured performances has also been achieved using EM simulation. In general, the measured performances challenge those exhibited by state-of-the-art micromachined inductors with similar inductance values. However, the proposed planar geometry is more robust compared to published developments of suspended or out-of-plane assembled architectures, and consequently can withstand violent mechanical shocks and vibrations and simplifies the packaging procedure of the final device. Based on the various trends issued from RF characterization, a library of about 500 inductors with inductance values ranging from 0.5 to 20 nH has been established. Moreover, a set of design rules aiming at the improvement of the performances from a layout point of view has been delineated. The library of inductor performances as a function of the layout parameters has enabled the design of inductors tailored for a given inductance value. As a further step of the research, lumped-element baluns have been fabricated by co-integrating optimized inductors with MIM capacitors so as to form low-pass and high-pass filter sections. The proposed baluns target the ISM frequency band (2400-2480 MHz) and are designed for operating in a 50single-ended/100 balanced environment. Typical values of the amplitude imbalance within the frequency band of interest are 0.45-0.55 dB, whereas the phase imbalance is less than 2°. The reflection loss at the single-ended port, S11 is found to be generally better than -20 dB at 2.4 GHz. Moreover, the single-to-differential insertion loss, Sds21 ranges from -0.8 to -1.0 dB. In general, the performances exhibited by the proposed baluns are comparable to those reported by micromachined baluns of similar type. Based on the achieved performances, fabricated inductors and baluns are suitable building-blocks dedicated to low-power wireless communication applications.
Thèse de doctorat : Université de Neuchâtel, 2006 ; 1902
Keywords: systèmes de communication sans fils; faible consommation de puissance; inductance; balun; microfabrication; microusinage; silicium haute résistivité; Pyrex; substrat à faibles pertes; aluminium; argent; facteur de qualité (Q); circuit équivalent; extraction de paramètres; circuit différentiel; paramètres S en mode mixte; simulation électromagnétique; Sonnet; wireless communication systems; low-power consumption; inductor; balun; microfabrication; micromachining; high-resistivity silicon; Pyrex; low-loss substrate; aluminum; silver; Q-factor; equivalent circuit; parameter extraction; differential circuit; mixed-mode S-parameters; electromagnetic simulation; Sonnet